Analysis of Differentiation and Innovation Strategy Development to Enhance Business Competitive Advantage - Hidayati, Nur; Wardhani, Rike Kusuma; Afrianto, Dadang; Nurrahma, Avinta Ika (Universitas Islam Kadiri, 2025)
Batik businesses in Indonesia show quite tight competition, including batik businesses in Kediri. This condition creates business opportunities in increasing competitive advantage in the same product but has more value that can increase competitive advantage in business. Rumah Batik Lochatara Business is committed to continuing to raise the cultural values ​​and natural wealth in Kediri through its unique motifs. This study aims to analyze differentiation and innovation strategies to increase competitive advantage in business at Rumah Batik Lochatara Kediri. The method used is qualitative descriptive analysis using Porter's value chain model to identify competitive advantages. Data collection techniques using observation techniques, interviews and related documentation. The results of the study show that the differentiation strategy of Lochatara batik can be seen from two dimensions of differentiation, namely personnel and image. And from the marketing innovation side. These two strategies are obtained from competitive advantages. Differentiation strategy by optimizing HR competencies and strengthening the image towards the international market. Product innovation is increasingly diverse, as well as the expansion of marketing and improvement of marketing technology used.